Economic and Land Use Impacts of Synthetic Dairy Production on a Dairy-intensive Economy: New Technology Moo-ving in - Winchester, Niven; White, D (Wiley, 2026)
Synthetic dairy products are promoted as an environmentally sustainable alternative to conventional dairy goods. This paper examines the potential economic, employment and land use impacts of large-scale synthetic dairy production on Aotearoa New Zealand—the world's leading dairy exporter. Using a global, economy-wide model, we simulate a case in which synthetic dairy products are cost-competitive with conventional dairy products. Our results show that, under this scenario, New Zealand's GDP would decline by 0.5%–0.7%, and national welfare would fall by 1.2%–1.5%, with significant employment impacts on dairy-related and other sectors. The reallocation of dairy land to other uses offers limited mitigation, as global shifts in production depress the prices of other agricultural commodities. Moreover, policies aimed at preserving dairy employment are costly. These findings suggest that, if synthetic dairy products are produced at scale, policy should prioritise adaptation strategies—such as retraining and skills development—to support workers and landowners in adjusting to the resulting changes.
Keywords: 38 Economics; 3801 Applied Economics; 15 Life on Land; Agricultural Economics & Policy; 3801 Applied economics; agricultural policy; agricultural technology; computable general equilibrium; land use